Proceedings on International Symposium on Microalloyed Bar and Forging Steeels, August 26-29, 1990, Hamilton, Canada - International Symposium on Microalloyed Bar and Forging Steel (1990 : Ontario, Canada); Finn, M. (Warrendale, PA: the Iron and Steel Society of AIME, 1990)
22